2020
DOI: 10.1111/anu.13186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary carbohydrate level on growth performance, innate immunity, antioxidant ability and hypoxia resistant of brook trout Salvelinus fontinalis

Abstract: Juvenile brook trout were fed on six isonitrogenous and isolipidic diets, containing graded levels of gelatinized corn starch (50, 100, 150, 200, 250, 300 g/kg diet) for 81 days. Cellulose was used to compensate carbohydrate loss. The weight gain, specific growth rate and protein efficiency ratio increased as the dietary carbohydrate level increased from 50 to 150 g/kg, but decreased thereafter (p < .05). Quadratic regression analysis revealed that the optimum dietary carbohydrate level was in the range of 187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
4
1
0
Order By: Relevance
“…The results showed that the high cornstarch diet negatively affected the immune response of tilapia. This result is consistent with the findings of Zhang et al 32 that excessive dietary carbohydrate intake (> 250 g/kg) may decrease innate immunity status in brook trout. Lysozyme, as an important part of animal immune defense, is often used as an immune index of fish 41,42 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the high cornstarch diet negatively affected the immune response of tilapia. This result is consistent with the findings of Zhang et al 32 that excessive dietary carbohydrate intake (> 250 g/kg) may decrease innate immunity status in brook trout. Lysozyme, as an important part of animal immune defense, is often used as an immune index of fish 41,42 .…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, feeding tilapia with a high cornstarch diet seems to elicit strong stress symptoms. The results of previous studies on antioxidant stress of juvenile black carp 16 , Wuchang bream 31 , brook trout 32 , and largemouth bass 33 fed with high starch diet were similar to those of this study. These studies showed that the higher the activity of antioxidant enzymes, the better the health status of aquatic animals, and the better the metabolic balance 16 , 22 .…”
Section: Discussionsupporting
confidence: 90%
“…This also confirmed that a high-carbohydrate diet caused lipid peroxidation. Similar results were found in fish fed a high-carbohydrate diet, such as M. amblycephala [ 33 ], Salvelinus fontinalis [ 44 ] and Micropterus salmoides [ 11 ]. Besides, SOD activity and T-AOC in the liver were determined to evaluate to evaluate the effect of carbohydrate levels on the antioxidant capacity of O. mykiss .…”
Section: Discussionsupporting
confidence: 76%
“…Yilmaz [13] demonstrated that 270 g/kg potato starch supplementation negatively affected lysozyme activity in O. mykiss. Similar results have reported in S. fontinalis and E. ilishaeformis fed with a high carbohydrate diet [44,46]. The findings of this study indicated that highcarbohydrate diet impaired the immune ability of O. mykiss.…”
supporting
confidence: 90%
“…This latter purpose leads to the release of brook trout in the natural environment as invasive species, which has an adverse ecological impact on the local ecosystem and fauna. Several studies have been conducted on this fish species concerning such topics as distribution [ 23 ], production performance [ 24 ], and sanitary conditions [ 25 , 26 ]. Although several aspects have been investigated with respect to this species, to the best of our knowledge, there are currently no studies concerning the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%